Education of Patriotism Values through Poetry : The Heroic Journey of Cut Nyak Dien - Zahara, Rosina; Setiawati, Nanda Ayu; Anita, Lenny; Mutia, Fahlila (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
One of the famous heroes of Aceh for her role in resisting colonialism is Cut Nyak Dien, who joined the fighters in direct opposition to the colonizers. Cut Nyak Dien continued to lead the resistance against the Dutch despite being a woman. She was feared by the Dutch for her ability to ignite the spirit of resistance among the Acehnese people. The patriotism upheld by Cut Nyak Dien is characterized by a deep love and loyalty for her homeland. Moreover, she was willing to sacrifice everything. In education, students should possess a high level of enthusiasm for learning in order to achieve high academic achievements. This article adopts a descriptive-analytical approach based on data gathered through literature review from various written sources. Thus, aspirations can be realized. The spirit of patriotism encompasses a never-surrender attitude, willingness to sacrifice, and unwavering determination that will bring prosperity and progress in the pursuit of the nation's ideals.